‘SEEDBOX HOGS’ AND ‘RATIO WHORES’: DISCUSSIONS OVER FILE SHARING STRATEGIES IN PRIVATE BITTORRENT COMMUNITIES - John, Nicholas (AoIR Selected Papers of Internet Research, 2015)
This paper is about the ways that members of private BitTorrent sites talk about the mechanisms used to monitor the extent to which they are sharing files in a reciprocal fashion.